(untitled) - Finegan, Edward (Stamford, CT, 2015)
This text explains what human language is and how it works, giving you a look into the multiple fascinating and surprising facets of this uniquely human trait. You find many opportunities to ask your own questions and explore the language in use all around you.
Ngôn ngữ học dẫn luận
Keywords: Ngôn ngữ học,Linguistics